Fano resonances in metallic grating coupled whispering gallery mode resonator - Luan, Feng (2014)
We experimentally demonstrate robust coupling of a metallic grating to the whispering gallery mode (WGM) of a microsphere resonator. The metallic grating coupled resonator forms a hybrid system that generates Fano resonances. Through theoretical modeling and experimental demonstration, we analyze this vertically coupled Fano-WGM structure. It is found that the Fano resonances originate from the interaction between the high-Q WGM and direct reflection of the grating. The Fano resonance shape is found to depend on the polarization state of the incident wave.